Fungsi Ekoleksikon Kecantikan dalam Lontar Bali Indrani Sastra - Ni Luh Sutjiati Beratha; Ni Wayan Sukarini; I Made Rajeg (Universitas Udayana, 2020)
This article analyses the phenomena of language related to the prescription of beauty from Balinese Traditional Manuscript (Lontar) entitled Lontar Indrani Sastra (Indrani Sastra Manuscript). The beauty of recipe in the Lontar Indrani Sastra is an ancestry cultural inheritance which has been already merged with the lives of the Balinese. Bali is famous because has conserved traditional manuscripts that become cultural heritage of the island. This article does not only apply the method of library research and field research but also descriptive qualitative method. The theory that is used to analyze the data is the theory of language functions. The function of beauty ecolexicon in the Lontar Indrani Sastra can be divided into three functions, namely (1) informative function, (2) interactive function, and (3) imaginative function. The informative function relates to various information about beauty prescription plants, body parts that can be treated and methods of treatment. Interactive functions are found through dialogue between Dewi Saci and Rukmini. Similarly, imaginative functions are discovered through the use of metaphors such as crocodile's calla (panggal buaya) and the Arjuna ecolexicons.